Histopathological and immunophenotypical criteria for the diagnosis of Sézary syndrome in differentiation from other erythrodermic skin diseases: a European Organisation for Research and Treatment of Cancer (EORTC) Cutaneous Lymphoma Task Force Study of 97 cases. (1st July 2015) - Klemke, C.D.; Booken, N.; Weiss, C.; Nicolay, J.P.; Goerdt, S.; Felcht, M.; Géraud, C.; Kempf, W.; Assaf, C.; Ortonne, N.; Battistella, M.; Bagot, M.; et al.
Summary: Background: Patients with erythrodermic disease are a diagnostic challenge regarding the clinical and histological differential diagnosis. Objectives: To evaluate histopathological and immunohistochemical diagnostic markers for Sézary syndrome. Methods: Ninety‐seven erythrodermic cases [Sézary syndrome (SS), n = 57; erythrodermic inflammatory dermatoses (EIDs), n = 40] were collected by the EORTC Cutaneous Lymphoma Task Force histopathology group. Evaluation criteria were (i) epidermal and dermal changes; (ii) morphology of the infiltrate; (iii) immunohistochemical analysis of marker loss (CD2, CD3, CD4, CD5 and CD7); (iv) bystander infiltrate by staining for CD8, FOXP3 and CD25; and (v) expression of Ki‐67, CD30, PD‐1 and MUM‐1. Results: The workshop panel made a correct diagnosis of SS in 51% of cases (cutaneous T‐cell lymphoma 81%) and of EID in 80% without clinical or laboratory data. Histology revealed a significantly increased degree of epidermotropism ( P < 0·001) and more intraepidermal atypical lymphocytes ( P = 0·0014) in SS biopsies compared with EID. Pautrier microabscesses were seen only in SS (23%) and not in EID ( P = 0·0012). SS showed significantly more dermal cerebriform and blastic lymphocytes than EID. Immunohistochemistry revealed a significant loss of CD7 expression (< 50%) in 33 of 51 (65%) cases of SS compared with two of 35 (6%) EID ( P < 0·001). The lymphocytic infiltrate in SS skin samples was found significantly to express PD‐1 ( P = 0·0053), MUM‐1 ( P = 0·0017) and Ki‐67 ( P < 0·001), and showed less infiltration of CD8 + lymphocytes ( P < 0·001). A multivariate analysis identified CD7 loss, increased numbers of small cerebriform lymphocytes, low numbers of CD8 + lymphocytes and increased proliferation (Ki‐67 + lymphocytes) as the strongest indicators for the diagnosis of SS. Conclusions: A number of different histological and immunophenotypical criteria are required to differentiate between SS and EIDs.